Transformasi Digital dan Inovasi Kemasan: Strategi Peningkatan Daya Saing UMKM Gula Merah dan Keripik di Desa Pelanggiran Laut Tador - Arifin, Indra Welly; Masyitah, Emi; Harahap, Hastuti Handayani; Rajagukguk, Frederick Rudy Sentosa; Rusmewahni, Rusmewahni; Nainggolan, Benhart; Hadi, Budiman; Karunia, Ade Mulia; Yuanda, Putri; Kurniawan, Reza (Community Service Progress, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Pelanggiran Laut Tador Village, particularly brown sugar and chip producers, have great potential thanks to the availability of local raw materials. However, their competitiveness is hampered by classic problems: very simple product packaging and a marketing strategy limited to word-of-mouth. This community service activity, implemented through the Real Work Lecture (KKN) program, aims to increase the competitiveness of these MSMEs through two main interventions: packaging innovation (rebranding) and marketing digitalization. The implementation methods include socialization, training, and direct mentoring. The results of the activity show significant transformations in branding and marketing aspects. New, more modern, hygienic, and informative packaging has been successfully designed and produced, namely standing pouch packaging for "Keripik Bu Isam" and besek and jar packaging (liquid sugar) for the Brown Sugar MSME. In addition, digital marketing assets have been created in the form of location registration on Google Maps, social media accounts (Facebook and Instagram), WhatsApp Business, and an e-commerce store (Shopee). This program has successfully increased MSMEs' understanding of the importance of branding and opened broader market access through digital platforms.